Narcismus: Teorie, výzkumy a možnosti jeho měření - František Bartoš (AntropoWebzin, 2009)
The article focuses on psychological and sociological theories of narcissism. We draw on traditional authors like Freud, Kohut, Kernberg, Fromm and Horney, but we also focus on contemporary psychologists like J. Beck and Rhodewalt. Our main intention is to show narcissism not only as a psychological disorder, but primarily as a social phenomenon. Therefore, we mention authors of sociological theories of narcissism, such as Lash, Sennett, Lipovetsky and Giddens. Our text is also oriented to measuring narcissism as a cultural phenomenon. We analyse scores, results, limits and hypothesis of existing tests trying to summarize the most important findings in empirical research of social consequences of narcissism.